PENGEMBANGAN MODUL BERBASIS FENOMENA SOSIAL UNTUK MENINGKATKAN MINAT BELAJAR MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - Sistriana, Sistriana; Aunurrahman, Aunurrahman; Usman, Andy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the development of modules based on social phenomena through the development of modules based on social phenomena on the material Diversity, Religion, Race, and Intergroup within the Unity in Diversity Frame, and to see how the implementation and interest in learning by using social phenomenon-based modules with subjects Class VII student research. The research method used in this research is the development research method by combining the Borg & Gall development model with the Dick & Carrey learning design model. Data obtained through interviews, observations and tests targeting the research subjects. The flow of the implementation of this research through three main stages, namely (1) Stage of product development plan, which includes analysis of learning objectives, learning analysis, identification of student characteristics, formulating objectives and planning of learning media, (2) Stage of product development, which includes product development, develop test instruments, develop learning strategies, develop and select teaching materials, design and develop evaluation drafts, Revise learning packages, and (3) Trial and revision stages, which include small group trials, initial product revisions, medium scale tests, revisions the second product, and a large scale product. The results showed a high percentage of implementation of learning activities at 83.33% in the activities of students. The increase in interest in learning can be seen from the enthusiastic and active attitude shown by students in using and discussing examples of social phenomena that are presented. In addition, an increase in interest was obtained from the questionnaire scoring. The first scoring through learning activities using textbooks obtained an average score of 2.60 which included a low interest category, and the second suspension on learning activities using social phenomenon-based modules obtained an average score of 4.18 which included the learning interest category that was high. Through antusia and activeness of students in using modules based on social phenomena the percentage of mastery learning can be increased, from 33.33% in the pre-test implementation to 86.67% at the post-test.                       Key Word : Social Phenomenon, Interest In Learning, Modules,